THE ESSENTIAL APPROACHES AND METHODS OF TEACHING MUSIC - Kenjebaeva Sabira Saylauovna (European Journal of Humanities and Educational Advancements, 2022)
Music plays an important role in our cultural life and in the development of human beings. Proper organization of the activities of all the senses is very important in the reception and acquisition of knowledge. The more members of the senses are involved, the easier it is to know. Demonstration is also an important law of music teaching, as the nature of this science requires more demonstration. This article discusses about the essential approaches and methods of teaching music